Representasi Estetika Batik Sumatera Selatan: Koleksi Museum Balaputera Dewa - Mukhsin Patriansah; Valentinus Verdianto; Nizar Riansyah (Besaung : Jurnal Seni Desain dan Budaya, 2025)
Textile crafts in South Sumatra have existed since the era of Sriwijaya and developed rapidly hundreds of years ago, particularly during the Palembang Sultanate period, one of which is batik preserved in the collection of the Balaputra Dewa Museum. The museum plays an important role as a medium for education, conservation, and cultural promotion at both national and international levels. The displayed collection serves as a means of cultural diplomacy that showcases the richness of South Sumatra’s art, history, and traditions to the outside world. South Sumatran batik holds a long historical value and experienced significant growth during the Palembang Sultanate era. The urgency of this research problem lies in the lack of academic documentation that elaborates on its aesthetic values, both intrinsic and extrinsic. As a cultural product, South Sumatran batik reflects the natural wealth, history, and culture of the local community. The research method used is qualitative with a descriptive approach. Data collection techniques include observation, in-depth interviews, documentation, and literature study to obtain information. The stages of data analysis involve data identification, data reduction, data analysis, and synthesis. The theoretical approaches employed are Stuart Hall’s representation theory and Jakob Sumardjo’s aesthetic theory to address the formulated research problems. The results of the study show that the batik collection at the Balaputra Dewa Museum generally features distinctive South Sumatran motifs that represent the natural environment, traditions, and belief systems of the local community. Thus, South Sumatran batik serves as a unique cultural identity with philosophical value, making it important to continuously preserve through scientific documentation, art education, and the active role of museums.